Political Robbery and Armed Robbery in Nigeria: A Comparative Approach - Egharevba, Edebiri Stanley; Osayande, Sunny; Odemwingie, Osahon (Advances in Social Sciences Research Journal, 2022)
The incidences of armed robbery in Nigeria have attained gross sinister dimension following the introduction of more sophisticated weapons. Armed robbery is a serious criminal offence which deserves grave sanctions, and so is political robbery. In fact, political robbery deserves more sanction because it is far worse than armed robbery and could be proven to be precursor to armed robbery and other social vices. Handlers of the Political sphere are laden with the responsibility of proper management of the nation’s common patrimony. However, this particular function as observed in some cases, has been grossly bastardized as it has become a medium of parochial but stupendous financial aggrandizement for self and family enhancement to the detriment of the general populace. This paper brings to the fore how political robbery (corruption) engenders social vices like armed robbery, kidnapping, etc. as its cases crawls without a conclusive end. The paper quizzes the similarities and differences between political robbery and armed robbery – which are basically two sides of a coin, but are accorded disproportionate sanctions. While political robbers usually get a slap-on-the-wrist sentence or a back pocket fine, armed robbers are daily railroaded to prisons.